Comparison between Fistulotomy vs Fistulotomy with Marsupialization in Simple Low Anal Fistulae: A Randomized Control Trial - Shazia Khan, Nadia Shahid, Jabbar Ahmed Qureshi, Batool Zehra Asjad, Khurram Baqqai, Yasir Murtaza (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of fistulotomy with marsupialization vs fistulotomy alone in the treatment of simple low lying anal fistula in terms of wound healing and postoperative pain. Study Design: Randomized control trial Place and Duration: Department of General Surgery, JPMC Karachi, duration of Study was 6 months from 23rd Aug 2020 to 23rd Feb 2021. Methodology: Sixty patients of either gender having ages 25-60 years presented with low anal fistula were included in this study. Detailed demographics were recorded after taking informed written consent from all the patients. Patients were divided in to two groups. Fistulotomy was performed on 30 patients in group A and fistulotomy with marsupialization was performed on 30 patients in group B. Patients were asked to choose envelop labelled treatment A and treatment B for the randomization. All patients were followed up on 24 hours after surgery and on weekly interval up to 4 weeks to determine the outcomes in terms of wound healing and pain score. Data was analyzed by SPSS 23.0. Results: In group A mean age of patients was 43.633+8.568 years while in group B mean age was 41.800+9.813 years. The mean Pain score after 24 hours in group A was 6.100+0.922 while in group B it was 5.033+0.718 with overall mean Pain score after 24 hours of 5.566+0.980. The mean Pain score after 5th day in group A was 4.266+0.639 while in group B it was 2.833+0.698 with overall mean Pain score after 5th day of 3.550+0.981. In Group A efficacy was achieved in 4 patients (6.7%) while in Group B efficacy was achieved in 14 (23.3%) patients. Conclusion: Marsupialization of the wound after fistulotomy for low anal fistula results in faster wound healing and less mean post operative pain as compare to fistulotomy alone. Keywords: Low Anal Fistula, Marsupialization, Fistulotomy, Pain, Wound Healing